Investigating G-quadruplex structures in RPGR gene: Implications for understanding X-linked retinal degeneration - Luigi Donato; Concetta Scimone; Simona Alibrandi; Domenico Mordà; Ivan Anchesi; Sergio Zaccaria Scalinci; Carmela Rinaldi; Rosalia D'Angelo; Antonina Sidoti (Heliyon, 2024)
Aims: This pilot study investigates the potential pathogenic role of G-quadruplex (G4) structures in RPGR-associated retinal degeneration, starting from a case of suspected X-linked form affected family. We hypothesize that the stabilization of these structures might alter DNA replication and transcription, inducing genetic instability and influencing gene expression. Main methods: We conducted whole genome amplification experiments and next-generation sequencing to detect the blockade of polymerase activity by G4 structures. Our specific focus was the RPGR gene, which hosts a high concentration of predicted G4-forming motifs and is implicated in most X-linked retinal degeneration cases. To understand the potential interference of G4 structures, we applied computational and 3D molecular modeling to visualize interferences in DNA replication and transcription regulation. Key findings: Our data confirmed the obstruction of DNA polymerase enzymes by G4 structures, particularly when stabilized by the compound pyridostatin. This obstruction was evident in the reduced amplification of RPGR gene regions and a shift in the start/end sites of putative G4 motifs. Moreover, the modeling indicated a potential disruption of critical promoter elements and RNA polymerase binding, which could drastically alter gene expression. Significance: Our findings suggest that G4 formation in the RPGR gene could lead to genetic instability and affect the expression of RPGR, contributing to retinal dystrophy. Moreover, this study underscores the broader implications of G4 structures in other genetic disorders. Improved understanding of G4 structures could reveal novel therapeutic targets to combat genetic disorders, promoting the advancement of personalized medicine and precision health.